KEMAS ULANG INFORMASI UNTUK PEMENUHAN KEBUTUHAN INFORMASI USAHA KECIL MENENGAH: TINJAUAN ANALISIS DI PDII-LIPI - Tupan, Tupan; Nashihuddin, Wahid (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2015)
This purposed of study to determine: 1) the types of information packaging products; 2) the process of information repackaging; and 3) the complied effort to the user information needs of smart scale enterprises (UKM) through PDII-LIPI information packs. Data of this study is a descriptive. Data collected by a discussion with the users or subscribers of information repackaging products of PDII-LIPI. The collected data are then be identified, analyzed, and interpreted the results and discussion chapter. The results of this study are known: 1) the types of information repackaging products of PDII-LIPI, namely: paket informasi teknologi, informasi kilat, pohon industri, panduan usaha, tinjauan literatur, fokus informasi indonesia, dan film animasi; 2) the process of making the package of information repackaging PDII-LIPI, namely the determination of topics, literature searching, analysis of the literature, making the design/template, duplication of information packing, and report generation; and 3) the efforts of institutions to complied the information needs of UKM through the product of information repackaging, namely: promotion, identification of needs, choosing the sources of information, product offerings, product evaluation utilization, and create innovative policies. In principle that the packaging of the information provided and created by PDII-LIPI had oriented by information needs of users, in particular to meet the UKM information needs.